Return migration and remittances : developing a Caribbean perspective - Stinner, William F. ed. (Research Institute on Immigration and Ethnic Studies WashingtonUS, 1982)
Papers drawn from Caribbean Studies Association Meetings in 1980 and 1982 as well as a Latin American Studies Association Meeting in 1982.